Common Fixed Point Theorems and Attractive Point Theorems with the Split Equilibrium Problem in Banach Spaces - Nutchari Niyamosot (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This main results of this dissertation is divided into two parts. In the rst part, we introduce and study some algorithms for nding a common element of the solution set of the split equilibrium problem and a common xed points set of nonlinear mappings in Banach spaces. For the second part, we prove a basic property of the set of attractive points in Banach spaces. Moreover, we introduce and study some algorithms for nding a common element of the solution set of the split equilibrium problem and a set of attractive point of nonlinear mappings in Banach spaces.